Education Environment and Role Transition of Internationally Educated Nurses Enrolled in a Practical Nursing Bridging Program in Ontario, Canada - Cruz, Edward Venzon; Quicho, Rosario F.; Ibañez, Edwin D. (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2022)
The purpose of this study is to explore a practical nursing bridging program’s education environment and the role transition of internationally educated nurses (IENs) who were enrolled full-time at a community college in Toronto, Canada, during the winter semester of school year 2018–2019. A survey questionnaire consisting of three parts was used to gather data from 68 IEN students who volunteered to participate in this study. Descriptive statistics and multiple regression analysis were used to analyze data. Participants’ responses to the open-ended question “Could you please list any problems/issues you have encountered in the bridging program?” were thematically analyzed. Results indicate that all bridging program education environment components, as well as role transition subscales, were described as “agree.” There is a significant relationship between the respondents’ perception of learning within their bridging program’s education environment and role transition. However, views on teachers and atmosphere, as well as academic and social self-perception, seemed insignificant predictors of role transition. Participants’ responses to the open-ended question were analyzed and grouped into four themes: concern with teachers, program content issues, program pace, and financial issues.